Effect of rate and temperature on the mechanical properties of epoxy BADGE reinforced with carbon nanotubes. (15th October 2018) - Reis, J.M.L.; Lima, R.P.; Vidal, S.D.
Abstract: The purpose of this work is to investigate the behavior of the epoxy diglycidyl ether of bisphenol A (BADGE) reinforced with carbon nanotubes when tested in tensile and flexural modes at different cross-head rates and temperatures. Tensile and flexural tests were performed under three temperatures (25 °C, 50 °C and 75 °C), varying the cross-head rate (0.5 mm/min, 5.0 mm/min and 50 mm/min) for tensile and (0.2 mm/min, 2.0 mm/min and 20 mm/min) for flexural at each designated temperature. Also, the glass transition temperature was observed, which helped understand the change in the behavior of the material during tests. An analytical mathematical model was proposed to predict the tensile and flexural strength and the model results were compared with the experimental results showing great accuracy.